Ideación Suicida e Inteligencia Emocional en pacientes que acuden a consulta psicológica al Centro de Salud N°3 de Loja, periodo 2022 - Veintimilla Conde, Noelia Elizabeth (2022)
Suicide is a problem that can affect any person regardless of race, sex or social status, the spectrum of suicide begins in most cases with suicidal desires that are identified as a warning sign to identify the risk. Poor emotional regulation and attention constitute a risk factor for the presence of suicidal ideation considered as the first stage of suicide. The general objective of the present study was to determine the relationship between suicidal ideation and emotional intelligence in patients of the psychology service of the Health Center N°3, it was carried out under a quantitative, descriptive approach, using a non-experimental, cross-sectional design and a correlational scope. As for the selection of the sample, inclusive and exclusive criteria were taken into account, leaving 68 patients to whom the Beck Scale for Suicide Ideation (SSI) was applied and Trait Meta-Mood Scale (TMMS-24). Regarding the results obtained, it was found that most of the participants presented suicidal ideation at medium levels, followed by some patients who presented ideation at a low level. On the other hand, the presence of suicidal ideation is related to high levels of attention and low levels of emotional repair, establishing positive and negative correlations respectively. It is clear that the dimensions of emotional intelligence may influence suicidal ideation; however, they are not the only factor to consider to determine its emergence